2015
DOI: 10.1038/pcan.2015.24
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic ethanol diffusion: comparison of two injection methods using ex vivo human prostates

Abstract: This study shows that freshly harvested human prostates can be used to evaluate new treatments using intraprostatic injection. Similar to in vivo canine experiments, the ethanol lesion sizes were significantly bigger with the use of a MiHFC when compared with a standard single lumen needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Thus, while these ex-vivo results are instructive of prostatic injection distribution, clinical studies are required to obtain reliable representation as to the relative contribution of the different flow mechanisms identified in these ex-vivo intraprostatic injections. However, these ex-vivo and prior comparative results of porous and standard needles indicate the porous needles provide improved distribution with the prostate [ 9 , 10 ], including one in-vivo study [ 11 ], all of which have shown porous needle superiority over standard needle injections.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while these ex-vivo results are instructive of prostatic injection distribution, clinical studies are required to obtain reliable representation as to the relative contribution of the different flow mechanisms identified in these ex-vivo intraprostatic injections. However, these ex-vivo and prior comparative results of porous and standard needles indicate the porous needles provide improved distribution with the prostate [ 9 , 10 ], including one in-vivo study [ 11 ], all of which have shown porous needle superiority over standard needle injections.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the prostatic pseudocapsule, acts as a barrier to the diffusion of injected 96% ethanol (EtOH), thus presenting an advantage over temperature-based focal treatment options ( 6 ). We have also documented that in contrast to a standard hollow core needle with a single opening at the tip, intraprostatic injection using a needle with a porous wall allows for diffusion of EtOH along the entirety of the 1 - 3 cm long porous segment, improving injectant distribution ( 7 , 8 ). These findings provide a strong foundation for further exploration of the porous needle for intraprostatic delivery of PCa therapy.…”
Section: Introductionmentioning
confidence: 99%